Information Presentation Pattern, Information Order and Framing Effect in Taking Investment Decisions - Mochammad Zahid Muzammil Hadi; Luciana Spica Almilia; Riski Aprilia Nita (The Indonesian Journal of Accounting Research, 2019)
The aims of this study are to examines the pattern of information presentation, the order of information and framing effect in investment decision making. the pattern of information presentation and the order of information explained by belief adjustment model developed by Hogarth and Einhorn (1992), beside that framing effect explained by prospect theory, fuzzy trace theory and probabilistic mental model. This study used experiment design 2x2x2 mixed design. Total subjects in this study were 104 students from STIE Perbanas Surabaya consisting of 90 students bachelor degrees of accounting and 14 students bachelor degrees of management. This study uses a pencil based experiment which filling out the questionare that was answered manually by participants.the results show that: (1) there are bias judgement especially recency effect in the presentation of step by step with the framing condition appropriate in information; (2) there are bias judgement when gives the presentation of step by step with the framing condition appropriate and not appropriate in information, and (3) when do mix of the pattern of information presentation with framing condition appropriate in information bias judgement happened. Overall this results show that the belief adjustment model developed by Hogarth and Einhorn (1992), prospect theory, fuzzy trace theory and probabilistic mental model is partially hold in investment decision making.